Antiretroviral Activity of fucoidans extracted from the Brown Seaweed Adenocystis utricularis - Trinchero Hernandez, Juan Sebastian (2009)
Treatment of human immunodeficiency virus type 1 (HIV-1, causative agent of AIDS) infection represents a major challenge in antiviral therapeutics. Many difficulties are associated with the treatment, including toxicity, resistance and high costs. Taking this into account, research for novel compounds able to overcome these limitations is needed. Sulfated polysaccharides appear to be interesting, given their abundance as components of seaweeds. Herein, a series of fractions obtained from the brown seaweed Adenocystis utricularis was analysed for in vitro anti-HIV-1 activity. These fractions, which have anti-herpes simplex virus activity, were determined previously to belong to the family of fucoidans, sulfated polysaccharides obtained from the cell walls of brown seaweeds. Assays in human PBMC primary cell culture demonstrated that two of the five fractions analysed had potent anti-HIV-1 activity both against WT and drug-resistant HIV-1 strains. For active fractions, it was also shown that the inhibitory effect was not due to an inactivating effect on the viral particle (i.e. no virucidal activity was detected) but rather to a blockade of early events of viral replication. Given these encouraging results, these seaweed-derived fractions appear as good candidates for further studies on their potential for in vivo therapy and/or prophylaxis of HIV-1 infection.